Perlindungan Hukum Terkait Jaminan Sosial Pekerja Ride-Hailing: Studi Komparatif Indonesia dan Malaysia - Wanda Putri Sukawan; Ariawan Ariawan (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The development of the digital economy has driven the growth of ride-hailing workers as part of the gig economy in Indonesia and Malaysia. However, the flexible nature of employment relationships under partnership schemes raises issues regarding legal protection, particularly concerning workers’ social security. This study aims to analyze legal protection for social security of ride-hailing workers in Indonesia and to analyze the social security arrangements for ride-hailing workers in Malaysia based on the Gig Workers Act 2025. This study employs a normative legal research method with a descriptive-analytical approach. The data used consists of secondary data, comprising primary legal sources, secondary legal sources, and tertiary legal sources. Data collection was conducted through a literature review using legislative, conceptual, and comparative approaches. The data were analyzed using qualitative-normative analysis techniques. The results indicate that social security protection for ride-hailing workers in Indonesia remains partial because ride-hailing workers are classified as partners and thus do not receive full labor protection. Social security protection still depends on voluntary enrollment in the BPJS Ketenagakerjaan, and there is no explicit obligation for platform companies to cover workers’ social security contributions. In contrast, Malaysia, through the Gig Workers Act 2025, has begun to establish a specific legal framework for gig workers, including provisions regarding social safety net protections. Although it has not yet equated gig workers with formal workers, Malaysia has granted specific legal recognition to gig workers and established a more systematic protection mechanism. This study contributes to providing a comparative analysis of social security protection models for ride-hailing workers in Indonesia and Malaysia as a basis for evaluating digital labor law reforms in Indonesia.